Antiproliferative mechanism of cervical cancer cells (hela) treated with biological-active subfraction from quercus infectoria extract - Abdullah, Hasmah (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2017)
Cervical cancer is placed at the fourth most frequent cancer among women worldwide, which was estimated approximately 530, 000 new cases in 2012. This type of cancer has become one of the leading causes of cancer death among women worldwide. Conventional and modern cancer treatment nowadays comes with negative and adverse side effects to the patients. Therefore, lot of studies have been conducted to search for new alternative treatment which is more safe and effective such as utilisation of natural product based medications. Previous studied revealed various pharmacological activities of Quercus Infectoria (QI) galls or manjakani including anticancer activity. However, the mechanism of action lay behind was not well explained. Therefore, in this present study, QI gall was selected for the evaluation of cytotoxic activity and cell death mode of action. In this study, QI was extracted using different types of organic solvents before being tested for cytotoxicity activity and mode of cell death. MTT assay was used to determine cytotoxic activity for n-hexane (QJH), ethyl acetate (QIEA) and methanol (QIM) of QI galls extracts against cervical cancer (Hela). Cytotoxic activity of QI extracts also tested against normal fibroblast (L929) cell line to determine cytotoxic effects and cytoselective properties. Meanwhile, DMSO-treated cells served as negative control while cisplatin-treated cells served as positive control. After that, dose-response graph was plotted to determine IC50 values. Observation on nuclear morphology, apoptotic percentage and detection of apoptotic protein expressions were also conducted. Moreover, phytochemical screening analysis had been carried out to determine bioactive groups that present in the most potent extract. From the findings, QIEA extract exhibited better cytotoxic activity with best growth inhibition against Hela cells (IC50 value= 6.33 ± 0.33 µg/ml) compared to other extracts and showed cytoselective property as no cytoxicity observed in the treated normal fibroblast (L929) cells. As for the phytochemical analysis of QIEA extract, it was revealed the presence of tannin, alkaloids, glycosides, saponins, terpenoids, flavonoids and phenolic compounds The QIEA extract was then purified and resulted two compounds 4-0 methylgallic acid (MGA) and gallic acid (GA). The most potent antiproliferative activity was exhibited by MGA sub fraction with IC50 II ±0.58 Jlg/ml. The current study also revealed that Hela cells treated with MGA subfraction has undergone apoptosis as exerted by the alteration of nuclear morphology and the presence of apoptotic bodies as well as the increment of apoptosis rate in the treated cells. Furthermore, MGA subfraction triggered apoptosis through upregulation of tumor suppression protein p53 , with down regulation of Bcl-2 expression and facilitated the apoptosis execution through caspase-3 activation . In conclusion, the purification of QIEA has resulted two biologicaly active subfraction namely MGA and GA. It was cleared that MGA subfraction reduced Hela cell growth through induction of apoptosis.